Scientific Pedagogical Basis Of Improving The Pedagogical System In Developing The Quality Of Physical Endurance At Students - Khudoiberganov Javlonbek Soatboy oglu (Research Parks Publishers, 2022)
This article summarizes the scientific and pedagogical basis for improving the pedagogical system in the development of physical endurance qualities in student youth.